2014
DOI: 10.1017/s1047951114001218
|View full text |Cite
|
Sign up to set email alerts
|

Living with CHD: quality of life (QOL) in early adult life

Abstract: Female patients and patients with poor academic performance and poor social support have worse psychosocial adjustment and perception of quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 32 publications
(54 reference statements)
4
20
0
1
Order By: Relevance
“…This study showed that German-speaking children and adolescents with CHD perceive statistically higher HRQoL than their healthy peers and that there were no differences between diagnostic subgroups and severity classes. Our findings are consistent with previous studies that showed even higher HRQoL in patients with CHD 10–12. Various parameters are attributed to subjective high HRQoL, such as social support, family environment,12 peers, school and community22 or high sense of coherence 23 24.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This study showed that German-speaking children and adolescents with CHD perceive statistically higher HRQoL than their healthy peers and that there were no differences between diagnostic subgroups and severity classes. Our findings are consistent with previous studies that showed even higher HRQoL in patients with CHD 10–12. Various parameters are attributed to subjective high HRQoL, such as social support, family environment,12 peers, school and community22 or high sense of coherence 23 24.…”
Section: Discussionsupporting
confidence: 93%
“…In children and adolescents with CHD, the data regarding HRQoL are inconsistent. Some studies report worse HRQoL in patients with CHD,6–8 while others describe equal or even higher scores in meta-analysis9 and primary studies 10–13. The lack of comparability among the available studies is owed to poor methodological standardisation, use of different types of questionnaires, heterogeneity of the examined cohort, small sample sizes or non-existence or inappropriate control group.…”
Section: Introductionmentioning
confidence: 99%
“…As observed in this study, a negative association between pharmacological treatment and QOL has been demonstrated in the physical domain. A possible explanation would be that the use of medication is associated with a lower autonomy of the patient, which in turn reduces QOL [53][54][55] .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with well-controlled CHD (adult and children) were reported to have QOL comparable to that in healthy individuals [17]. However, the QOL in complex or cyanotic CHD is reportedly poor [18], it was also found that patient subjective QOL assessment was corroborated by objective laboratory and imaging results.…”
Section: Discussionmentioning
confidence: 97%